ANALISIS PRODUKSI REBUNG BAMBU BETUNG (Dendrocalamus asper) DI KAMPUNG URIEMI DISTIK RASIEI KABUPATEN TELUK WONDAMA - Kadam, Lince; Agus Irianto Sumule; Obadja A. Fenetiruma (Sosio Agri Papua, 2025)
This study aims to analyze the production process of betung bamboo shoots (Dendrocalamus asper) and determine the income earned by farmers in Uriemi Village, Rasiei District, Teluk Wondama Regency. The research method used is descriptive with a case study approach, involving 22 bamboo shoot farmers selected through purposive sampling. Data was collected through interviews and direct observations, then analyzed quantitatively and qualitatively. The results showed that bamboo shoot production is carried out throughout the year, with an average harvest yield of 25 kg per harvest. The average farmer's revenue from bamboo shoot farming is IDR 8,318,182 per year, with a net income of IDR 5,789,614 per year after deducting production costs. It is recommended that farmers receive training on bamboo shoot processing and product development to increase added value and community welfare.